Bearing 'financial responsibility' for the Government and the Party: C.D. Deshmukh (1950–56) & T.T. Krishnamachari (1956–58). Issue 4 (1st October 2020) - Ankit, Rakesh
ABSTRACT: Of the 17 years (1946–64) Jawaharlal Nehru was India's Prime Minister, his Congress Party government had a senior politician holding the Finance Ministry for only 5: Morarji Desai (1958–63). Otherwise, this crucial portfolio was held by a succession of experts; an illustration of consociational power sharing. This article is about two of those, C.D. Deshmukh and T.T. Krishnamachari, and some of their chequered governmental experiences. Through these, it seeks to cast a critical light on the changing contours of relations between and within the party and the government in the economic sphere during its decade of political dominance.